Effect of Denture Cleansers on The Roughness of Heat-Or Auto Cured Denture Liners - MESE, AYSE (Asian Journal of Chemistry, 2010)
This study investigated the effect of short (24 h) and long term (6 months) exposure to a variety of commercially available denture cleanser solutions on the roughness of a variety of acrylic-and silicone-based resilient liners that were either heat-or auto-cured. The denture liners investigated were an acrylic-based heat-cured (Vertex Soft), acrylic-based auto-cured (Coe-Soft), a silicon-based heat-cured (Molloplast-B) and silicon-based auto-cured (Mollosil Plus) resilient liners. Cylindirical specimens (14 mm dia, 1 mm high) were made of each material, using 10 replications for each test condition. Immersion solutions consisted of distilled water (control) and those based on alcohol, chlorhexidine or an alkaline peroxide (dermacol, aqueous chlorhexidine, steradent) as a major active component. Specimens were fabricated according to manufacturer directions. Surface roughness were taken on all specimens at each time interval and then compared statisti-cally using fourway ANOVAs and Tukey HSD (α = 0.05). The results of this study indicated that in comparison with distilled water, significant effect on the roughness of the specimens were found after immersion in all of the denture cleanser solutions at 24 h and at 6 months. Specimens immersed in alkaline peroxide showed higher and significant roughness changes than those immersed in other cleanser solutions. It was also determined that roughness of resilient liner materials increased with time and significantly higher roughness was recorded at 6 months for the auto-cured specimens compared with their heat-cured counterparts. The increasing roughness was greatest in acrylic-based, auto-cured resilient liner in all cleansers especially in alkaline peroxide, which suggests that the use of this resilient liner may not provide long-term clinical success.